1998
DOI: 10.1086/305113
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeGoddard High Resolution Spectrograph Observations of the Be + sdO BinaryφPersei

Abstract: Mass transfer during the evolution of intermediate-mass stars in a close binary system can result in a rejuvenated and spun-up secondary star (which may appear as a rapidly rotating Be star) orbiting an unseen, stripped-down, remnant companion. One of the best candidates for such a system is the longperiod (127 days) binary / Per. Here we present new Hubble Space Telescope Goddard High Resolution Spectrograph spectra of / Per in several UV regions that show clearly for the Ðrst time the spectral signature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
155
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(169 citation statements)
references
References 27 publications
14
155
0
Order By: Relevance
“…We began making circular fits with the period derived by Božić et al (1995), P = 126.6731±0.0071 d, and we derived an orbital semiamplitude of K a = 11.4 ± 1.0 km s −1 . This agrees within the uncertainties with the value reported by Gies et al (1998), K a = 10.0 ± 0.8 km s −1 .…”
Section: Spectroscopic Orbital Determination From Radial Velocity Measupporting
confidence: 93%
See 2 more Smart Citations
“…We began making circular fits with the period derived by Božić et al (1995), P = 126.6731±0.0071 d, and we derived an orbital semiamplitude of K a = 11.4 ± 1.0 km s −1 . This agrees within the uncertainties with the value reported by Gies et al (1998), K a = 10.0 ± 0.8 km s −1 .…”
Section: Spectroscopic Orbital Determination From Radial Velocity Measupporting
confidence: 93%
“…They classified the primary star as B0.5e. The companion was finally confirmed by Gies et al (1998) thanks to high-resolution UV spectroscopy with the Hubble Space Telescope (HST). The subdwarf-to-Be flux ratio is 0.165±0.006 (resp.…”
Section: Main Characteristics Of ϕ Perseimentioning
confidence: 97%
See 1 more Smart Citation
“…If the secondary would be a normal late M dwarf corresponding to its mass, it would be fainter in the visual region by more than 10 mag and the only chance to search for it would be in the far IR region, where, however, the IR excess from the Be envelope can complicate the detection. However -if it were a hot subdwarf, similar to the one found for another Be binary ϕ Per by Gies et al (1998) -it might be observable in the optical region since the absolute visual magnitude of BU Tau is fainter for some 2 mag than for the ϕ Per B0.5e primary. Finally, a cool Rochelobe filling secondary seems improbable since it would probably produce binary eclipses.…”
Section: Bu Tau As a Spectroscopic Binarysupporting
confidence: 58%
“…Already Plavec (1976) pointed out that if all Be stars were binaries with Roche-lobe filling secondaries, one should observe more eclipsing binaries among them than what is actually observed. While Harmanec (1987) slightly weakened this objection, there is a stronger one: detailed studies of several known Be binaries (ϕ Per = HD 10516: Poeckert 1981, Gies et al 1998; V839 Her = 4 Her: Koubský et al 1997, for instance) clearly demonstrated that the secondaries in those binaries are not Roche-lobe filling objects but very small stars. The same is also true of binaries composed of a Be star and a compact, X-ray companion.…”
Section: Attempts To Explain the Be Phenomenonmentioning
confidence: 99%